Ethical values in the nursing profession as perceived by head nurses and staff nurses in public Hospitals, Banda Aceh, InDonesia - Yullyzar (Prince of Songkla University, 2014)
Thesis (M.N.S., Nursing Science)--Prince of Songkla University, 2013